Genomic and phenotypic characterisation of Listeria monocytogenes strains isolated from pig feces on farm and from pork meat at retail in France - Evelyne Boscher; Benjamin Félix; Alain Rincé; Patricia Legrandois; Lucas Sajan; Christophe Soumet; Martine Denis (PLoS ONE, 2026)
Listeria monocytogenes is an ubiquitous foodborne pathogen transmissible to humans through the consumption of contaminated products, including pork. In this study, we characterised the Listeria monocytogenes population circulating from the primary reservoir, pigs, to consumers in France. In 2008 and 2010, 147 strains from on-farm pig feces and 154 strains from retail pork meat were respectively isolated. Serogroups and clonal complexes (CC) were determined (n = 301), and 123 representative strains were further assessed for virulence, biofilm-forming ability, and resistance to Benzalkonium chloride (BC). Serogroup IIb, and CCs such as CC11, CC21, CC20, CC26, CC31, CC59, CC37, CC1 and CC77 strains predominated on farms, whereas serogroup IIc and IIa (respectively CC9 and CC121) were mainly recovered from retail meat. All 123 strains harbored the virulence-associated genes inlA , inlC, inlJ, plcA , prfA , actA , hlyA and iap. Overall virulence did not differ significantly between farm- and retail-derived strains; however, serogroup IVb strains were significantly more virulent, while serogroup IIc strains exhibited lower virulence. In our study, CC1 (mainly present in feces) and CC121 (present only on meat) showed the highest virulence level. Biofilm-forming ability was significantly higher in strains isolated from farm feces than in those from retail meat. Most meat strains, including CC121, CC9, CC14 and CC7, were more resistant to benzalkonium chloride than fecal strains. Our findings highlight the genetic and phenotypic evolution of the Listeria monocytogenes population along the pig-to-pork continuum. They suggest that strains persisting to the retail stage are more strongly associated with resistance to biocides than with robust biofilm formation in the food-processing environment. Contrary to expectations, our CC121 strains exhibited the highest level of virulence, even though this CC is reported hypovirulent.